2011
DOI: 10.1371/journal.pone.0023974
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of Condition-Dependent Male and Female Mate Choice in Zebra Finches

Abstract: In mating systems with social monogamy and obligatory bi-parental care, such as found in many songbird species, male and female fitness depends on the combined parental investment. Hence, both sexes should gain from choosing mates in high rather than low condition. However, theory also predicts that an individual's phenotypic quality can constrain choice, if low condition individuals cannot afford prolonged search efforts and/or face higher risk of rejection. In systems with mutual mate choice, the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 67 publications
2
31
1
Order By: Relevance
“…In contrast, in socially monogamous species where assortative mating occurs, looking for a high‐ranking male could result in a delay in pairing and laying date (Holveck & Riebel ; Holveck et al. ), and thus hinder the reproductive success. Pairing quickly with a male of the same quality as itself could be a better strategy for the female.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in socially monogamous species where assortative mating occurs, looking for a high‐ranking male could result in a delay in pairing and laying date (Holveck & Riebel ; Holveck et al. ), and thus hinder the reproductive success. Pairing quickly with a male of the same quality as itself could be a better strategy for the female.…”
Section: Discussionmentioning
confidence: 99%
“…Recent attempts to quantify the effects of developmental stress on female song preferences have concluded that developmental stress affects preference strength for unfamiliar songs, but not preference for a familiar song model [34], or that stress either has little or no effect on female preferences [35, 36], or that females prefer to mate assortatively, according to developmental background [37, 38]. If female preference strength is altered by developmental stress, due to changes in perception, discrimination or decision making then we would expect relaxed selection on the relevant male traits.…”
Section: Cognition Signalling and Mate Choicementioning
confidence: 99%
“…However, further studies would be needed to determine to what extent females can really use such information, given flock stability or the amount of attention they can allocate to the assessment of the quality of extra-pair mates [63]. Finally, the fitness consequences of pairing with good-or poor-condition males also deserve further investigation [26].…”
Section: (B) Body Condition and Song Ratementioning
confidence: 99%